Arrhythmias in Children with Acute Respiratory Viral Infections: Prevalence and Causes - Sabina Kh. Israfilova; Tatiana K. Kruchina; Gennadiy A. Novik ("Paediatrician" Publishers LLC, 2024)
The article presents literature review about arrhythmias in children with acute respiratory viral infections (ARVI). The search was carried out in such databases as PubMed, CyberLeninka, RSCI, etc. ARVI is the most common infectious disease in children and adults, and it can have severe course and various complications. Arrhythmias can be frequently revealed in children with ARVI, and most of them are transient. Life-threatening cardiac rhythm and conduction disorders (CRCD) may occur more rarely, especially in severe cases. Knowledge and interest in the pathophysiology of viral infections have increased significantly, including CRCD risk factors in ARVI, thanks to the data obtained during the analysis of COVID-19 clinical course and outcome. This review summarizes and analyzes data on CRCD prevalence and arrhythmogenesis causes in ARVI.